Searching for efficient and informative instruments to digitally monitor fraction learning: putting tests for fraction subconstruct knowledge and informal fraction knowledge on the test bench - Schadl, Constanze; Lindmeier, Anke (Frontiers in Education, 2025)
Fractions are a relevant yet complex topic of school mathematics. Fortunately, educational research issued rich knowledge of central concepts and associated students’ difficulties. Using this knowledge for monitoring learning and formative assessment could support students’ learning process. However, access to apt evidence-based tests is restricted, and paper-based testing limits their practical usability. The digital adaptation of paper-based tests may address these challenges due to affordances like automated test scoring. Further, digital tests may facilitate repeated test use necessary for monitoring and formative activities. The present contribution focuses on fraction subconstruct knowledge and informal fraction knowledge and is part of a systematic research effort to transform paper-based tests into a digital format. With two cross-sectional studies in Grades 6 (N = 233) and 5 (N = 271), each with three measurement points, we investigated the psychometric properties of adapted digital parallel tests regarding their suitability for repeated testing. The internal structure of the adapted digital tests proved to be comparable to that of the original paper-based tests in many, but not all, aspects. Parallel tests were found to be sufficiently parallel. The findings for the two focused constructs support that systematic efforts lead to usable tools for students’ fraction learning. The discussion considers how this supports the transformation of research findings to support the adoption of formative assessment.